PHYTOCHEMICAL SCREENING AND GASS CROMATOGRAPHY MASS SPECTROMETER (GC-MS) ANALYSIS ETHANOL EXTRACT OF PURPLE SWEET POTATO (Ipomoea batatas L.) - Surti Kurniasih; Dina Dyah Saputri (Journal of Science Innovare, 2019)
Purple sweet potato (Ipomoea batatas L.) leaves are extremely versatile that possesses high value. Sweet potato (Ipomoea batatas L.) leaves have secondary metabolism compounds that used as antibacterial and antifungal. The content of secondary metabolite compounds contained in plants an important role in providing antibacterial and antifungal activity so that this study was conducted to develop the utilization of purple sweet potato leaves through phytochemical screening. Phytochemical screening aims to provide an overview of the class of compounds contained in purple sweet potato leaf plants including of alkaloids, steroids-triterpenoids, saponins, flavonoids, and tannins test. Samples were taken from the local community of Bogor. The extract is made by extracting the simplicia of positive purple sweet potato leaves containing alkaloid, steroids-triterpenoids, saponins, flavonoids, and tannins. Further identification of active compounds was performed by Gass Cromatography-Mass Spectrometer (GC-MS) analysis to detect the active compound contained in purple sweet potato leaf extract more specifically. GC-MS analysis results show several active compounds including: 1.4-Benzenediol (CAS) Hydroquinone, Benzenesulfonic acid 4-hydroxy (CAS), Hexadecanoic acid (CAS) Palmitic acid.